As–Co–Ni sulfarsenides in Palaeogene basaltic cone sheets as sources of groundwater arsenic contamination in co. Louth, Ireland. (April 2021) - Russell, Alexander; McDermott, Frank; McGrory, Ellen; Cooper, Mark; Henry, Tiernan; Morrison, Liam
Abstract: Elevated arsenic concentrations (up to 19 μg L −1 ) occur in private groundwater wells in fractured bedrock aquifers close to the contact between Silurian greywackes of the Longford-Down Terrane, and the Palaeogene Slieve Gullion and Carlingford igneous complexes in NE Ireland. Palaeogene basaltic intrusions intersected in two drill cores were found to contain up to 80 mg kg −1 arsenic; concentrations that are elevated compared with the global averages for basalt. Fine grained (c. 5 μm) disseminated sulfarsenides, associated with cobalt and nickel were identified in the basalts as the primary sources of groundwater arsenic in this fractured bedrock aquifer system. Many of the high-As waters exhibit relatively high pH, arguing against a simple single-stage sulphide oxidation model for arsenic solubilisation. This observation coupled with the widespread presence of iron oxyhydroxide coatings on natural rock fractures intersected in the drill cores suggests a multi-stage As mobilisation process. This interpretation envisages sulfarsenide mineral oxidation, adsorption of dissolved As to iron oxyhydroxide mineral surfaces, and finally desorptive release of oxyanion As species from these surfaces as waters evolve to higher pH as a result of water-rock reactions. Highlights: Basaltic cone sheets in the area are enriched in arsenic compared to global averages. Cobalt- and nickel-bearing sulfarsenide minerals are the primary sources of arsenic. Pyrite and sulfarsenide weathering is required to explain water As/SO4 ratios. Most waters with elevated arsenic have high rather than low pH. Arsenic adsorption to Fe-oxyhydroxide surfaces followed by desorptive release.